Accelerated ischemic vascular retinopathy after intravitreally injected bevacizumab for central retinal vein occlusion in elderly patients - Isola V (Dove Medical Press, 2013)
Vincenzo Isola,1 Alfredo Pece,1,2 Claudio Massironi,1 Simone Reposi,1 Fabio Dimastrogiovanni11Department of Ophthalmology, Melegnano Hospital, 2Fondazione Retina 3000, Milano, ItalyBackground: Ischemic changes in the retinal circulation are an uncommon but severe adverse vascular reaction to intravitreal bevacizumab (Avastin®, Genentech, San Francisco, CA, USA/Roche, Basel, Switzerland) for central retinal vein occlusion (CRVO). In the two cases reported here, ischemic changes in the retina vasculature following intravitreal bevacizumab for CRVO were observed with the aim of describing the clinical and angiographic features of these changes.Methods: Two elderly patients with recent-onset CRVO received one off-label intravitreal injection of bevacizumab 0.05 mL/1.25 mg.Results: In Case 1, the patient's pre-treatment visual acuity was 20/400. At 3 weeks post injection, the patient could count fingers at a distance of 1 ft (30 cm) and fluorescein angiography showed reduction in intraretinal hemorrhages and areas of retinal non-perfusion. However, at 6 weeks these were markedly increased compared with those seen in the photograph taken 3 weeks after treatment. In Case 2, the patient's pre-treatment visual acuity was 20/200. At 1 month post injection, vision had decreased to 20/400 and fluorescein angiography showed severe macular ischemia with a remarkable capillary dropout throughout the macula.Conclusion: Ischemic retinal injury may be an uncommon but severe adverse vascular reaction to intravitreal bevacizumab for CRVO. Although progression of retinal ischemia in CRVO could be observed shortly after intravitreal bevacizumab, whether this is a drug- or procedure-related effect or part of the natural history of the condition remains uncertain.Keywords: Avastin, ischemia, macular infarction, intraretinal hemorrhage, retinal non-perfusion